Comparison of Oral and Vaginal Route of Misoprostol for Induction of Labour at Term - Raazia Rauf, Maliha Sadaf, Asma Shaheen (Journal of Rawalpindi Medical College, 2012)
Background: To compare the Induction – Delivery interval between Oral and Vaginal route of Misoprostol at term. Methods: In this comparative study , one hundred women at term with indications for induction of labour and Bishop score < 5, having no other obstetric and maternal contraindications for induction of labour were randomly assigned to receive Misoprostol 50 g orally and 50 g vaginally every 6 hours for 24 hours for a total of four doses. Repeated doses were given until Bishop score > 8 was achieved or spontaneous rupture of membranes occurred. Student’s t test was applied to compare induction delivery interval between oral and vaginal groups and statistical significance was assigned to P- value < 0.05. Results: The median induction to delivery interval time was significantly shorter with vaginal Misoprostol (11.0 h), compared with oral Misoprostol (14.1 h, p= 0.036). There was no difference between two routes of administration with respect to rates of hyperstimulation or neonatal asphyxia. Conclusions: Compared with oral Misoprostol, vaginal Misoprostol for induction of labour at term results in a shorter induction to delivery interval time. There were more caesarean section in the vaginal Misoprostol group.